Annual transcriptome dynamics in natural environments reveals plant seasonal adaptation - Nagano, Atsushi J.; Kawagoe, Tetsuhiro; Sugisaka, Jiro; Honjo, Mie N.; Iwayama, Koji; Kudoh, Hiroshi (Nature plants, 2019)
As most organisms have evolved in seasonal environments, their environmental responses should be adapted to seasonal transitions. Here we show that the combination of temperature and day length shapes the seasonal dynamics of the transcriptome and adaptation to seasonal environments in a natural habitat of a perennial plant Arabidopsis halleri subsp. gemmifera . Weekly transcriptomes for two years and bihourly diurnal transcriptomes on the four equinoxes/solstices, identified 2,879 and 7,185 seasonally- and diurnally-oscillating genes, respectively. Dominance of annual temperature changes for defining seasonal oscillations of gene expressions was indicated by controlled environment experiments manipulating the natural 1.5-month lag of temperature behind day length. We found that plants have higher fitness in ‘natural’ chambers than in ‘unnatural’ chambers simulating in-phase and anti-phase oscillations between temperature and day length. Seasonal temperature responses were disturbed in unnatural chambers. Our results demonstrate how plants use multiple types of environmental information to adapt to seasonal environments. A study examined transcriptome dynamics of Arabidopsis halleri weekly for two years and bihourly for the four equinoxes/solstices, revealing that the change of temperature rather than day length dominantly defines the seasonal transcriptome oscillations.